2013
DOI: 10.1155/2013/214140
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Peak Flood Discharge for an Ungauged River: A Case Study of the Kunur River, West Bengal

Abstract: Due to unavailability of sufficient discharge data for many rivers, hydrologists have used indirect methods for deriving flood discharge amount, that is, application of channel geometry and hydrological models, for the estimation of peak discharge in the selected ungauged river basin(s) in their research/project works. This paper has studied the estimation of peak flood discharge of the Kunur River Basin, a major tributary of the Ajay River in the lower Gangetic plain. To achieve this objective, field measurem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 16 publications
3
9
0
Order By: Relevance
“…Compared to other studies, the MAE for peak discharge was 39.8 m 3 /s and was reasonable when compared to the MAE value observed [72]. Similarly, RMSE estimated as 45.48 m 3 /s suggests a reasonable performance when compared to RMSE values recorded in Roy and Mistri [68]. Given the limited data and the performance of the model, model prediction was deemed reliable for modelling other historical and future hydrologic changes.…”
Section: Model Validationsupporting
confidence: 47%
See 2 more Smart Citations
“…Compared to other studies, the MAE for peak discharge was 39.8 m 3 /s and was reasonable when compared to the MAE value observed [72]. Similarly, RMSE estimated as 45.48 m 3 /s suggests a reasonable performance when compared to RMSE values recorded in Roy and Mistri [68]. Given the limited data and the performance of the model, model prediction was deemed reliable for modelling other historical and future hydrologic changes.…”
Section: Model Validationsupporting
confidence: 47%
“…This is a reliable alternative for determining parameters X and K and for simulating open channel discharge downstream in ungagged river channels. K equals the flood wave time travel through the reach and X equals the dimensionless weight (0 ≤ X ≤ 0.5) [68].…”
Section: Runoff Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…where A is the area of the basin equal to 23.17 km 2 , L is the length of the main thalweg equal to 11.705 km and ∆H is the difference in mean elevation from outlet's elevation equal to 197.17 m, as derived from the ArcGIS design. Another empirical formula widely used for calculating T c (h) is the one of Kirpich, which was developed for rural watersheds in Tennessee ranging from 0.004 km 2 to 0.453 km 2 and having slopes from 3% to 10% [41], as follows:…”
Section: Simulation Of the Precipitation Event Of 17 October 2006 Usimentioning
confidence: 99%
“…Average daily rainfall data (1996-2016) of Sarpang rain gauge station were collected from DHMS, Bhutan and peak discharge was calculated by Kinematic Wave Parameter (KWP) for Flow Velocity and Discharge Estimation method (Rodriguez-Iturbe et al 1982) shown in equation (1) 11 . Average slope of channel as 0.4 and channel outlet cross section of 600 m 2 were calculated from stream profile and stream cross section respectively which were generated in HEC-RAS software.…”
Section: Peak Dischargementioning
confidence: 99%